2008
DOI: 10.1103/physreve.78.026124
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an expanding circular cavity and the failure of amorphous solids

Abstract: Recently, the existence and properties of unbounded cavity modes, resulting in extensive plastic deformation failure of two-dimensional sheets of amorphous media, were discussed in the context of the athermal Shear-Transformation-Zones (STZ) theory. These modes pertain to perfect circular symmetry of the cavity and the stress conditions. In this paper we study the shape stability of the expanding circular cavity against perturbations, in both the unbounded and the bounded growth regimes (for the latter the unp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The simulation method presented can be used as a basis for further study. It can be readily adapted to a wide variety of geometries, and we have written a preliminary version in polar coordinates for computing STZ elastoplasticity problems involving circular and elliptical holes in an infinite medium, for which a variety of exact and asymptotic solutions have been examined [21,23]. We also aim to study some newer versions of the STZ theory [24,25,26], and hope to incorporate orientational effects when a non-isotropic STZ density is employed.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation method presented can be used as a basis for further study. It can be readily adapted to a wide variety of geometries, and we have written a preliminary version in polar coordinates for computing STZ elastoplasticity problems involving circular and elliptical holes in an infinite medium, for which a variety of exact and asymptotic solutions have been examined [21,23]. We also aim to study some newer versions of the STZ theory [24,25,26], and hope to incorporate orientational effects when a non-isotropic STZ density is employed.…”
Section: Resultsmentioning
confidence: 99%
“…These studies observed evidence of the curvature dependence of the surface energy on the measured cavitation rate, an effect that has itself been the subject of a significant amount of study [19][20][21][22]. One particularly notable contribution from simulation was the mapping out of the point at which the gas-liquid spinodal dips below the glass line and the glass must become unstable to cavitation [23].Continuum mechanics approaches to modeling the kinetics of cavitation have been developed over many years by numerous researchers [6,[24][25][26][27][28][29][30]. Often preexisting cavities are assumed to exist due to voids, inclusions, or intersections of grains, and the effect of surface energy is neglected.…”
mentioning
confidence: 99%
“…Continuum mechanics approaches to modeling the kinetics of cavitation have been developed over many years by numerous researchers [6,[24][25][26][27][28][29][30]. Often preexisting cavities are assumed to exist due to voids, inclusions, or intersections of grains, and the effect of surface energy is neglected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture toughness is the critical value of the stress-intensity-factor, K Ic , at which crack propagation initiates and global failure occurs. Recent work [33,[38][39][40][41][42][43][44][45][46][47] suggests that this onset (and in fact also the subsequent propagation [33]) is controlled by a local cavitation instability occurring when the hydrostatic tension 1 3 trσ surpasses a threshold level σ c . We adopt this failure criterion here.…”
Section: Problem Formulationmentioning
confidence: 99%